Strategic addition of rosemary essential oil in natural rubber-toughened poly(lactic acid)/cinnamon oil blends for antimicrobial packaging - Bathumalai Shamene; See Min Tee; Noor Afizah Rosli (Future Foods)
Bacterial spoilage in fruits and vegetables has emphasised the importance of extending the shelf life of food and ensuring a secure and dependable food supply that requires suitable packaging. This study presents an innovative biodegradable film for active food packaging, incorporating poly(lactic acid) (PLA) and natural rubber (NR) with cinnamon essential oil (CEO) and rosemary essential oil (REO). Although past research has examined individual essential oils in packaging, the combined effects of CEO and REO in a PLA/NR matrix remain unexplored. The influence of different CEO-to-REO ratios on the properties of PLA/NR/CEO blends was comprehensively investigated. Tensile tests showed that incorporating REO substantially improved the mechanical properties, with PLA/NR/1CEO:4REO and PLA/NR/1CEO:1REO exhibiting the highest tensile strength and elongation at break, respectively. Notably, REO incorporation effectively reduced essential oil release in aqueous environments, enabling controlled hydrolytic degradation of the PLA/NR/CEO blend. Thermal analysis showed that higher REO content increased both the thermal stability and crystallinity of the PLA/NR/CEO blends, addressing a common limitation in biodegradable packaging materials. All active films showed good antimicrobial properties against Escherichia coli and Bacillus cereus. Overall, the addition of REO to the PLA/NR/CEO blend synergistically improves the mechanical and thermal properties of the active films.